Trends and periodicities of monsoon and annual rainfall districts of Haryana State and Delhi - LAL, BHUKAN; DUGGAL , Y. M.; RAM, PANCHU (MAUSAM, 1992)
Analysis of southwest monsoon (June to September) and annual rainfall of 12 districts of Haryana and Delhi based on fixed number of raingauge stations (36) has been made for 90-year period (1901-1990) in order to search for trends and periodicities in the rainfall. It is seen that monsoon and annual rainfall have a similar variability and is least where rainfall is maximum. It is also observed that frequency distribution of monsoon rainfall is not normal in two districts, viz., Kurukshetra and Sirsa. Positive trend is noticed in monsoon rainfall of Rohtak and Kurukshetra and annual rainfall of Delhi. Increase in the mean rainfall for 45 years period showed a gradient from first to second from the east central to the western parts of the State with a maximum value over the east central parts. Low-pass filter analysis suggests that the trend is not linear but oscillatory consisting of periods of 10years or more. The spectral analysis indicates a significant cycle of range 5.5 to 8 ..6 years mainly in eastern and southwestern districts of the State. QBO IS also observed over some districts of the State.